ANALYSIS PERFORMANCE OF EQUITY MUTUAL FUNDS AT INDONESIANS CAPITAL MARKET ACCORDING TO SHARPE, TREYNOR AND JENSEN METHODS - Ukhriyawati, Catur Fatchu (Universitas Riau Kepulauan, 2012)
Mutual Funds constitutes the way of investment that relatively new in Indonesia. It appeared since commonly the investors have difficulties to undergo the own investment on the securities. The difficulties are it is necessary to do various analyses and monitor continually the market condition that spending many times. Through mutual funds, an investor is able to put his fund to be managed Investment Companies and then widely to diversify and give the profit to the investors. Equity mutual funds is the collection of community fund that was invested into various stocks by Investment Manager. Equity mutual funds has higher-risk compared to the other mutual funds, however, give the high-return level. Analysis method of equity mutual funds performance is Sharpe, Treynor and Jensen methods. Since the performance measurement is not only regarded from the amount of mutual funds return but also borne-risk.The performance of equity mutual funds in Indonesia, with period January 2004 – December 2006 is: in year of 2004, equity mutual funds that has the highest performance, according to Sharpe Method, is Platinum Saham, followed by Fortis Ekuitas, then Si Dana Saham. According to Treynor and Jensen methods that has the highest performance is Platinum Saham, followed by Fortis Ekuitas, then Si Dana Saham. In year of 2005, reksa dana stock that has the highest performance, according to Sharpe, is Platinum Saham, followed by Fortis Ekuitas, then Trim Kapital. The highest performance, according to Treynor and Jensen methods, has been possessed by Fortis Ekuitas, followed by Platinum Saham, then Trim Kapital. In year 2006, equity mutual funds that has the highest performance, according to Sharpe method, is Platinum Saham, followed by Trim Kapital, and then Dana Saham. According to Treynor and Jensen methods that has the highest performance is Platinum Saham, followed by Trim Kapital, and then Fortis Ekuitas. Performance rank according to Treynor and Jensen methods is rather equal since the calculation of two methods above are using beta (b).It is better to use the Sharpe method than Treynor and Jensen method in the equity mutual funds period of 2004-2006, since the risk was more influence by total risk (totaling the systematic risk and not systematic).